Assessment of Zero Waste Management Systems in Universities: Waste Reduction Efficiency and Environmental Benefits - Abdimutalip, Nurlibek; Toychibekova, Gaziza; Baeshova, Kulayhan; Aidarbekova, Zhanna (International Journal of Environmental Science and Green Technology, ISSN: 3080-8693, 2025)
This paper presents an assessment of waste generation on the campus using experimental and analytical methods, within the framework of the concept of "zero waste." The study is based on an analysis of campus infrastructure data from 2016 to 2024, using index and normalized methods. The indicator of specific intensity of waste generation (kg/m ²· year) was calculated. It was revealed that the optimization of the campus structure, carried out after 2018 and including a reduction in the area and number of buildings, did not lead to a commensurate decrease in the volume of generated waste. The largest specific generation of waste was found in food outlets and student dormitories, where the share of organic matter in waste is from 55 to 65%. Academic buildings form more stable flows, mainly consisting of paper and mixed waste. The data obtained indicate the primary influence of the functional purpose of objects and the characteristics of user behavior on the volume of waste, and not the spatial characteristics of the infrastructure. The possibility of using the university campus as a pilot project for the introduction and further expansion of zero waste strategies in the higher education system of Central Asia is being considered.